Vascular type Ehlers-Danlos syndrome is associated with platelet dysfunction and low vitamin D serum concentration. Issue 1 (December 2016) - Busch, Albert; Hoffjan, Sabine; Bergmann, Frauke; Hartung, Birgit; Jung, Helena; Hanel, Daniela; Tzschach, Andeas; Kadar, Janos; Kodolitsch, Yskert; Germer, Christoph-Thomas; Trobisch, Heiner; Strasser, Erwin; et al.
Abstract Background The vascular type represents a very rare, yet the clinically most fatal entity of Ehlers-Danlos syndrome (EDS). Patients are often admitted due to arterial bleedings and the friable tissue and the altered coagulation contribute to the challenge in treatment strategies. Until now there is little information about clotting characteristics that might influence hemostasis decisively and eventually worsen emergency situations. Results 22 vascular type EDS patients were studied for hemoglobin, platelet volume and count, Quick and activated partial thromboplastin time, fibrinogen, factor XIII, von Willebrand disease, vitamin D and platelet aggregation by modern standard laboratory methods. Results show a high prevalence of over 50 % for platelet aggregation disorders in vascular type EDS patients, especially for collagen and epinephrine induced tests, whereas the plasmatic cascade did not show any alterations. Additionally, more than half of the tested subjects showed low vitamin D serum levels, which might additionally affect vascular wall integrity. Conclusion The presented data underline the importance of detailed laboratory screening methods in vascular type EDS patients in order to allow for targeted application of platelet-interacting substances that might be of decisive benefit in the emergency setting.